Prevalence of phenotypic resistance of Staphylococcus aureus isolates to macrolide, lincosamide, streptogramin B, ketolid and linezolid antibiotics in Turkey - Adaleti,Riza (2010)
The incidence of drug-resistant pathogens differs greatly between countries according to differences in the usage of antibiotics. The purpose of this study was to investigate the phenotypic resistance of 321 methicillin resistance Staphylococcus aureus (MRSA) and 195 methicillin susceptible S. aureus (MSSA) in a total of 516 S. aureus strains to macrolide, lincosamide, streptogramin B (MLS B), ketolid, and linezolid. Disk diffusion method was applied to determine MLS B phenotype and susceptibility to different antibiotic agents. It was found that 54.6% of the isolates were resistant to erythromycin (ERSA), 48% to clindamycin, 55% to azithromycin, 58.7% to spiramycin, 34.7% to telithromycin, and 0.4% to quinupristin-dalfopristin, respectively. No strain resistant to linezolid was found. The prevalence of constitutive (cMLS B), inducible (IMLS B), and macrolides and type B streptogramins (M/MS B) among ERSA isolates (237 MRSA, 45 MSSA) was 69.6 %, 18.2%, and 12.2 % in MRSA and 28.9%, 40%, and 31.1% in MSSA, respectively. In conclusions, the prevalence of cMLS B was predominant in MRSA; while in MSSA strains, iMLS B and M/MS B phenotype were more higher than cMLS B phenotype resistance. The resistance to quinupristindalfopristin was very low, and linezolid was considered as the most effective antibiotic against all S.aureus strains.